Primary leiomyosarcoma of the sigmoid colon: Case report and review of literature - Narjisse Aichouni, MD (Elsevier, 2022)
Leiomyosarcomas of the sigmoid colon are aggressive and extremely rare tumors representing less than 0.1% of all colorectal malignancies. Few cases have been reported in the literature and their imaging features need to be more detailed. We report the case of a 70 year old male patient, smoker, with a history of arterial hypertension, admitted for abdominal pain and hypogastric mass. Computed tomography has shown a voluminous heterogeneously enhancing tumor process with a necrotic center, attached to the sigmoid wall, with multiple secondary peritoneal and hepatic masses. The anatomopathological examination of the biopsy sample with immunohistochemistry allowed the diagnosis of leiomyosarcoma of the sigmoid colon. Clinical presentation and radiological features of leiomyosarcomas are non-specific, and the definitive diagnosis is only established after an anatomopathological examination.